OP0088 COMORBIDITIES AS RISK FACTORS FOR RHEUMATOID ARTHRITIS (RA) AND ACCRUAL AFTER RA DIAGNOSIS. (June 2019) - Kronzer, Vanessa; Crowson, Cynthia S.; Sparks, Jeffrey; Myasoedova, Elena; Davis, John
Abstract : Background: Understanding the timeline of comorbidity development in patients with RA may inform disease pathogenesis and help identify targets for improving outcomes (1) . Objectives: We first aimed to compare the prevalence of a comprehensive list of comorbidities in RA cases versus controls. Second, we aimed to investigate the time association of comorbidity development relative to RA onset to identify which comorbidities might predispose to developing RA and comorbidities that might result from RA. Methods: We performed a case-control study using a biobank at a single center, identifying 821 cases of RA (143 incident) using a rules-based algorithm combining two diagnosis codes with use of a DMARD (PPV = 95%). We matched each case to three controls based on age, sex, and location of residence at the time of the biobank survey. Participants self-reported the presence or absence and age of onset for 77 comorbidities on the survey. Results: Among the 3, 276 RA cases and controls, mean age was 62 years, and 73% were female. Cases with RA had the same number of comorbidities as controls before RA diagnosis (median 1.0 vs 1.0, P = 0.49) but had more comorbidities by the time of the survey (median 5.0 vs 4.0, p < 0.001). At the time of the survey, several comorbidities were more common in participants with RA than controls (Table1). Cancer was not more common in RA cases than controls (31% vs 32%, p = 0.80), even among all cancer subtypes. The only comorbidities that tended to develop in the time period before RA diagnosis more often than controls were inflammatory bowel disease (1.9% vs 0.5%, p < 0.001) and type 1 diabetes (1.3% vs 0.4%, p = 0.01). In contrast, in the time period after RA diagnosis, myocardial infarctions were more common in cases with RA (3.8% vs 1.2%, p < 0.001) and hyperlipidemia was less common (11.4% vs 16.4%, p = 0.004) compared to controls. Conclusion: Many comorbidities were associated with RA, including several potentially novel comorbidities such as COPD, epilepsy, and acid reflux. RA was not associated with an increased risk of cancer. The increased occurrence of inflammatory bowel disease and type 1 diabetes prior to RA suggests either a predisposition to RA development or a shared immunological defect, meriting further study. References: [1] Gabriel SE, Michaud K. Epidemiological studies in incidence, prevalence, mortality, and comorbidity of the rheumatic diseases. Arthritis Res Ther. 2009;11(3):229. Acknowledgement: Funding for this project was provided by the Rheumatology Research Foundation Resident Research Preceptorship. We would also like to acknowledge the Mayo Clinic Center for Individualized Medicine Disclosure of Interests: Vanessa Kronzer: None declared, Cynthia S. Crowson: None declared, Jeffrey Sparks Grant/research support from: Bristol-Myers Squibb, Amgen, Consultant for: Optum, Elena Myasoedova Grant/research support from: Pfizer, John Davis Grant/research support from: Pfizer